Application of central composite design for optimization of the removal of humic substances using coconut copra - Terri Zhuan, Ean Lee; Chanida, Krongchai; Nurul Aida Lu, Bt Mohd Irwan Lu; Sila, Kittiwachana; Siong, Fong Sim (Springer Berlin Heidelberg, 2015)
Coconut copra is a potential biosorbent for removal of humic substances from peat swamp runoff. In this paper, response surface methodology was applied to evaluate the optimum conditions for removal of humic substances from peat swamp runoff using modified coconut copra. Batch adsorption experiments were conducted according to central composite design. Results show that the quadratic model is best fitted for predicting the removal efficiency with regression coefficients closer to 1 and a lower root mean square error. Dosage is found to have significant influence on the removal efficiency with p < 0.05. Response surface models further identified the optimum dosage, contact time and temperature at 4.56 g modified coconut copra per 100 mL peat swamp runoff, 42.9 min and 56.8 °C/329°K, respectively attaining the maximum removal efficiency of 88.19 %. The predicted removal efficiency was confirmed experimentally under the modelled optimum conditions; the removal efficiency attained (86.54 %) was in good agreement with the predicted value.